2017
DOI: 10.1007/s11605-017-3531-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Centralizing Gastric Cancer Surgery on Treatment, Morbidity, and Mortality

Abstract: IntroductionCentralization of gastric cancer surgery is thought to improve outcome and has been imposed in the Netherlands since 2012. This study analyzes the effect of centralization in terms of treatment outcome and survival in the Eastern part of the Netherlands.MethodsAll gastric cancer patients without distant metastases who underwent a gastrectomy in six hospitals in the Eastern part of the Netherlands between 2008 and 2011 (pre-centralization) and 2013–2016 (post-centralization) were selected from the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 30 publications
(37 reference statements)
4
41
0
Order By: Relevance
“…Other studies 14,15 showed that increased hospital volume was associated with lower postoperative mortality rates and improved survival after gastric cancer surgery. However, a Dutch study 16 , which included patients treated surgically in the eastern part of the country, did not find an improvement in overall survival after gastrectomy following centralization; this was probably related to the small number of patients investigated. Another study 17 also reported no association between hospital volume and long-term survival.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Other studies 14,15 showed that increased hospital volume was associated with lower postoperative mortality rates and improved survival after gastric cancer surgery. However, a Dutch study 16 , which included patients treated surgically in the eastern part of the country, did not find an improvement in overall survival after gastrectomy following centralization; this was probably related to the small number of patients investigated. Another study 17 also reported no association between hospital volume and long-term survival.…”
Section: Introductionmentioning
confidence: 93%
“…The results from previous studies investigating the effects of centralization of gastric cancer surgery on outcome are ambiguous. Studies from the UK and Denmark showed that patients who underwent gastrectomy in the period after centralization had a lower postoperative mortality rate and better overall survival than patients treated before centralization.…”
Section: Introductionmentioning
confidence: 98%
“…Of the 60 patients who underwent curative gastrectomy the overall operative mortality rate was 1.6%. Compared with countries with larger populations, a higher incidence of gastric cancer and mandated centralized units for the management of gastric cancer, our results benchmark satisfactorily . Two of the most important measures of surgical quality in gastric cancer surgery are the rate of R 0 resection and adequacy of lymph node resection (with at least 15 lymph nodes harvested the accepted standard) .…”
Section: Discussionmentioning
confidence: 51%
“…We have recently employed a sub‐specialty trained UGI surgeon trained in minimally invasive surgery and aim to offer laparoscopic surgery in between 30% and 50% of patients with gastric malignancy . Similarly, our use of neoadjuvant chemotherapy was also less than observed in overseas units during the study period . This largely reflects local oncology policy operating between 2010 and 2014.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation